2020
DOI: 10.1002/cche.10292
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics and protein quality of selected commercially obtained brown and yellow canary seed flours and prepared isolates

Abstract: Background and ObjectivesCanary seed is a true cereal crop and classified as a “novel” food for human consumption. To explore potential food applications, the current study focused on evaluating the functional and nutritional properties of flours and protein isolates from glabrous (yellow and brown) canary seed.FindingsThe proximate composition, total starch and total amylose contents of the flours from both brown and yellow seeds were not significantly different. Both flours shared similar pasting properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 30 publications
5
15
1
Order By: Relevance
“…Similar to canaryseed, lower number of polypeptide bands were visible in the gluten sample compared to the wheat flours, showing evidence of protein loss during processing. The polypeptide profiles of canaryseed isolates evaluated by Achouri et al (2020) and Moura et al (2020) showed clear differences in the polypeptide profiles to the current study, especially in high molecular weight glutelin and globulin region and lower molecular weight region <10 kDa, mainly representative of albumins. In these two studies, the canaryseed protein isolates were prepared using alkali extraction and isoelectric precipitation processes at different extraction pH levels whereas, a completely different process was used to prepare isolates in the present study.…”
Section: Structural Changes Flours and Isolatescontrasting
confidence: 75%
See 4 more Smart Citations
“…Similar to canaryseed, lower number of polypeptide bands were visible in the gluten sample compared to the wheat flours, showing evidence of protein loss during processing. The polypeptide profiles of canaryseed isolates evaluated by Achouri et al (2020) and Moura et al (2020) showed clear differences in the polypeptide profiles to the current study, especially in high molecular weight glutelin and globulin region and lower molecular weight region <10 kDa, mainly representative of albumins. In these two studies, the canaryseed protein isolates were prepared using alkali extraction and isoelectric precipitation processes at different extraction pH levels whereas, a completely different process was used to prepare isolates in the present study.…”
Section: Structural Changes Flours and Isolatescontrasting
confidence: 75%
“…However, they showed strong stability once formed. Overall, both whole and white canaryseed flour showed low solubility (~50% or less) and shared similar solubility trend with each other (Figure 5a, Moura et al, 2020). The maximum solubility of 50.5% and 45.2% was obtained for whole and white four, respectively at pH 2 whereas, the minimum solubility was observed at pH 5-7 (2%-5.6%) for both canaryseed flours.…”
Section: Techno-functional and Nutritional Properties Of Proteinssupporting
confidence: 55%
See 3 more Smart Citations